Diagnostic Accuracy of Fine Needle Aspiration Cytology of Thyroid Pathologies - Kunwar, Shova; Bajracharya, Barsha; Karmacharya, Kavita; Shrestha, Amar Narayan (Medical Journal of Shree Birendra Hospital, 2020)
Introduction: Fine needle aspiration cytology is considered as the gold standard for the diagnosis of thyroid nodules. This study aimed to evaluate and compare the accuracy of fine-needle aspiration cytology in the diagnosis of thyroid lesion by comparing it with the corresponding histopathologic diagnosis after thyroidectomy. Methods: This is a retrospective study conducted over five years at a teaching hospital in Kathmandu. Eighty-nine cases of FNAC of thyroid nodule with subsequent histopathological reports were reviewed. The corresponding reports were compared and the accuracy of FNAC diagnosis was evaluated. Results: 87% of the cases were females and the majority of cases were in the age group 41 to 50 years. Among 89 cases, 55 were reported as benign on cytology and 34 were reported as malignant. On histopathological examination, out of 55 cases diagnosed as benign on cytology, 47 cases were diagnosed as benign whereas eight cases were diagnosed as malignant. HPE of 34 cases diagnosed as malignant on cytology showed that 29 were malignant and five were benign. The false-positive rate was 9.6% and the false-negative rate was 21.6%. The sensitivity was 78.3% and specificity was 90.3%. The positive predictive value and negative predictive value were 85.2% and 85.4% respectively. The accuracy of FNAC in differentiating benign from malignant thyroid lesions was 85.3%. Conclusions: The findings of this study showed that FNAC is a sensitive method for the diagnosis of a solid thyroid lesion